RECONSTRUCTION OF STATUS AND AUTHORITY OF THE SHARIA COURT IN THE NATIONAL JUDICIAL SYSTEM BASED ON JUSTICE - Jufri Ghalib; Darwinsyah Minin (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Article 25 of Law No. 18 of 2001 on Special Autonomy for the Special Province of Aceh as Nanggroe Aceh Darussalam province mandated that the Islamic Law Judicial in Aceh province as part of the national judicial system undertaken by Mahkamah Syar‟iyah (Sharia Courts) free from the influence of any party. For the implementation of these norms, Presidential Decree No. 11 of 2003 specifies Pengadilan Agama (Religious Courts)  that had existed in the province of Aceh should be converted into Sharia Court and Pengadilan Tinggi Agama (High Courts of  Religious Courts) in Banda Aceh should be converted into Sharia Court of the Province of Nanggroe Aceh Darussalam. Sharia Court's authority is further stipulated by Aceh Qanun. The provisions of Article 25 of Law No. 18 of 2001 are then confirmed by Article 128 to Article 137 of Law Number 11 Year 2006 concerning the Government of Aceh. Specificity of Sharia Court in Aceh Province, among others, can be seen from its absolute competencies which is based on Islamic law in the national judicial system. Furthermore, Article 128 paragraph (3) of Law Number 11 Year 2006 concerning Aceh Government and Article 49 of the Qanun Aceh Province Number 10 Year 2002 regarding Islamic Law Judicial , make it clear that the absolute competencies of Sharia Court covers judge actions in ahwal al-syakhsiyah field (family law), mu'amalah (civil law) and jinayah (criminal law), which is based on Islamic law. Struggle enforceability instituting Islamic law formally in the province of Aceh in order to have a status in the state administration by law has been successfully agreed with the promulgation of  Law No. 18 of 2001 and Law No. 11 Year 2006. Granting authority to implement Islamic law, legally embodies the implementation of Law No. 44 of 1999 on Implementation Features Special Province of Aceh. Based on the background of historical studies Sharia Court which is now the place to resolve the problem of Muslims, and in view of the Sharia Court is judicative power under Article 128 paragraph (1) of Law Number 11 Year 2006 concerning Aceh Government included in the environment of religious judicial body under the Supreme Court by Act No. 48 of 2009 on judicial power which stipulates that judicial power is implemented by the four environments of judicial bodies, namely the Public Judicial Body, Religious Judicial Body, Military Judicial Body and State‟s Administrative Judicial Body.   Occurred a noticeable difference between the two laws in the judicial seat of Islamic law in Aceh in the order of the national judicial system. Law Number 11 Year 2006 seat Islamic Law Judicial as part of the national judicial system in religious judicial body, whereas Law Number 50 Year 2009 seat Islamic Law Judicials as a special court which is in the  two environmentals of judicial bodies, religious judicial body and public judicial body in accordance with its judicial authority being absolute competence. Settings on the Islamic Law Judicial  are different from one law with other legislation can lead to differences in interpretations. The differences in interpretation or disharmony of the legislation will result in the emergence of problems at the level of implementation. The problems that have been described above are taken as the reason to do research with the title " Reconstruction of Status and Authority of Sharia Courts in National Judicial System Based on Justice of Islamic Law "